Statistical characterization of structural demand under earthquake loading. Part 2: Robust estimation of the dispersion of the data - Xavier Romão (2012)
Performance-based earthquake engineering methodologies often require a probabilistic model of structural demand. Since observations masking the probability distribution of the majority of the data are frequently found, robust estimation methods are proposed to estimate the probabilistic model parameters (i.e., central value and dispersion). The performance of thirty-three robust dispersion estimators is evaluated, for different sample sizes, using the chord rotation, curvature, shear force, and inter-story drift demands obtained after analyzing five reinforced concrete structures under real earthquake records scaled to several intensities. Based on the results, combinations involving dispersion and central value (defined in a companion article) estimators are proposed